Investigations on the microstructure, tensile strength and high temperature corrosion behaviour of Inconel 625 and Inconel 718 dissimilar joints. (January 2017) - Ramkumar, K. Devendranath; Abraham, Winston Sunny; Viyash, Vedha; Arivazhagan, N.; Rabel, Arul Maximus
Graphical abstract: Highlights: Effect of Ni-Mo rich fillers on the control of laves phase in the dissimilar welds. Segregation of Mo rich phases in the inter-dendritic regions. Tensile strength of the weldments was superior than the base metals. Molten salt corrosion studies on the dissimilar joints exposed at 900 °C. Parent metal Inconel 718 exhibited lower corrosion resistance with spallation and blistering of oxide scales. Abstract: In this article, an attempt has been made to investigate the effect of fillers on the pulsed current gas tungsten arc welding (PCGTAW) of Inconel 625 and Inconel 718. Two different Ni-Mo rich fillers namely ERNiCrMo-4 and ERNiCrMo-10 were employed for joining 5 mm thick plates of Ni based super alloys. The deleterious Laves phase was completely suppressed, while using these fillers. Mo rich segregation was observed in the fusion zones for both the fillers without much depletion of Mo in the fusion matrix. Tensile failures were observed at the parent metal of Inconel 718 in both the cases. It was attested from the notch tensile studies that the notch strength ratio was greater than unity, which attested that the weldments were ductile in all conditions. Impact studies showed that the weldments employing ERNiCrMo-10 exhibited better impact toughness at room temperature conditions. Hot corrosion studies were performed on the coupons exposed in the synthetic molten salt environment of 60%Na2 SO4 –40%V2 O5 at 900 °C. Studies showed that both the parent metal Inconel 625 followed by the fusion zone of ERNiCrMo-10 exhibited better corrosion resistance in the high temperature environment. Surface analytical techniques were adopted to investigate the hot corroded species.